Social media Wołodymyra Zełenskiego a kreowanie wizerunku w dobie wojny ukraińsko-rosyjskiej - Narożna, Dominika (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2022)
W artykule autorka analizuje wizerunek Wołodymyra Zełenskiego w prowadzonych przez niego mediach społecznościowych (social mediach) w pierwszym miesiącu od agresji Rosji na Ukrainę. Wskazuje w jaki sposób uległ on zmianie, podaje przyczynę tych modyfikacji oraz określa sposoby kreowania wizerunku prezydenta Ukrainy. Odnosząc się do analizy zawartości treści poszczególnych wystąpień Wołodymyra Zełenskiego przy uwzględnieniu głosów polskich ekspertów obrazuje elementy mające wpływ na kształtowanie jego marki osobistej (personal branding).

In the article, the author analyzes the image of Volodymyr Zelensky in his social media in the first month after Russia’s aggression against Ukraine. It indicates how it has changed, gives the reasons for these modifications and defines the ways of creating the image of the President of Ukraine. Referring to the content analysis of the individual speeches of Volodymyr Zelensky, taking into account the opinions of Polish experts, it illustrates the elements influencing the formation of his personal brand.
Social media of Volodymyr Zelensky and creating the image during the Ukrainian-Russian war
Keywords: Wołodymyr Zełenski; wizerunek; social media; wojna ukraińsko-rosyjska; Volodymyr Zelensky; image; social media; Ukrainian-Russian war